Investigasi Sifat Mekanik terhadap Perbedaan Media Pendingin pada Proses Induction Hardening Baja AISI 1015 - Azmy, Ilham; Adhitya Muhamadika , Chandra (Politeknik Negeri Ujung Pandang, 2025)
AISI 1015 steels have been vigorously used to numerous automotive parts. Unfortunately, it has several mechanical shortcomings due to poor hardness, wear resistance, and strength. To tackle its crucial problem, the AISI 1015 steels have been treated by induction hardening treatment at 850 oC which subsequently cooling to the ambient temperature using different cooling media of water, salt bath, and oil. The as-prepared AISI 1015 steels were then investigated its mechanical properties involving spectrometry, microstructure observation, hardness, wear, and tensile test. The AISI 1015 treated steels after induction hardening in water cooling media exhibited intriguing microstructure of vast pearlite encircle ferrite matrix. The sample also garnered significant enhancements of hardness, wear resistance, and tensile properties. These superior mechanical characteristics are believed to be catered for the induction treatment using water cooling media which boost crystalline structure transformation deliberately. Therefore, this research affords significant promise for improved mechanical properties of the AISI 1015 steels.